2019
DOI: 10.3892/or.2019.7003
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and characterization of novel human oral squamous cell carcinoma cell lines from advanced‑stage tumors of buccal mucosa

Abstract: Oral squamous cell carcinoma (OSCC) is a leading cause of mortality in India owing to the high percentage of tobacco chewers, smokers and alcohol consumption. OSCC is highly heterogeneous in nature; therefore poses a challenge in the treatment of the patient. To better understand the heterogeneity of the tumors, an in vitro cell line model is required. However, the efficiency of establishing cell lines from the oral tumors is low. In the present study, three novel cell lines, namely ACOSC3, ACOSC4, and ACOSC16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 36 publications
0
13
0
1
Order By: Relevance
“…In addition, our spheroids showed keratin expression after 19 days of culture comparable to the xenograft mouse model suggesting that the cellular function of the moderately differentiated squamous cell carcinoma cell lines was maintained. Keratin expression has been used as a method for HNSCC model validation both in 2D and 3D culture models. …”
Section: Discussionmentioning
confidence: 99%
“…In addition, our spheroids showed keratin expression after 19 days of culture comparable to the xenograft mouse model suggesting that the cellular function of the moderately differentiated squamous cell carcinoma cell lines was maintained. Keratin expression has been used as a method for HNSCC model validation both in 2D and 3D culture models. …”
Section: Discussionmentioning
confidence: 99%
“…Various articles report the establishment of epithelial cell lines from patient samples. These epithelial cell lines were derived from different tissue origins, for example, buccal mucosa (15), gingivobuccal mucosa (14), oral cavity (3032), tongue (13,33), sinonasal (34), pyriform fossa (35), lower alveolus and retromolar trigone (33). To elucidate the impact of different mutations on tumor behaviour, recently 16 cell lines from HNSCC were established by Hayes et.al (36).…”
Section: Discussionmentioning
confidence: 99%
“…Certain studies have also reported directly digesting the tumor tissue and seeding the cell suspension (30,33). Majority of reports have described establishing primary cultures by explant culture method (1315,32,34). The current study also used explant culture method for MhCT12 and MhCT08 establishment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have used ACOSC3, ACOSC4 and ACOSC16 OSCC cell lines, which were recently established in our laboratory from the advanced stage treatment naïve buccal mucosa tumours [39]. For skin cancer, we have used the human squamous cell carcinoma (SCC) line A3886 obtained from Dr. Colin Jamora's Lab at Instem, Bengaluru [40].…”
Section: Methodsmentioning
confidence: 99%